Cohesive strategy and energy conversion efficiency analysis of bio-hythane production from corncob powder by two-stage anaerobic digestion process. (March 2020) - Zhang, Zhiping; Xu, Congcong; Zhang, Yue; Lu, Shijie; Guo, Lingkong; Zhang, Yan; Li, Yameng; Hu, Bing; He, Chao; Zhang, Quanguo
Highlights: Cohesive strategy for two stage bio-hythane production process was investigated. Suitable coupling time node realize the directional generation of bio-hythane. Effluents with different components were adopted for bio-methane production. Cogeneration of bio-H2 and bio-CH4 increases energy conversion efficiency. Abstract: In order to maximize the substrate conversion, co-production of hydrogen and methane from two-stage anaerobic digestion has attracted wide attention. In two-stage fermentation process, the cohesive strategy is considered as a key indicator for bio-hythane yield. In this work, corncob powder was utilized as raw material. The pH of fermentative broth, bio-hythane yield, gas production rate and energy conversion efficiency were taken as indexes. Under the directional control of bio-chemical reaction process, the effects of diverse coupling time nodes on the fermentation process and the bio-hythane co-production potential were investigated. The results showed that when the coupling time node was 48 h, hydrogen production potential and methane production potential were 22.29 mL/g TS and 141.14 mL/g TS, respectively. The hydrogen content in the bio-hythane was 13.64% which satisfied the hydrogen concentration requirement, and the energy conversion efficiency was 27.6%.